Teaching Language Sciences in Rehabilitation Secondary School Souss Massa, Regional Directorate - Taroudant, Kingdom of Morocco - Sico Pedagogic Approach - Ebayza, Zuhair (Journal of Educational and Psychological Sciences, 2018)
This research paper aims at shedding light upon the reality of teaching language sciences at the high school level. Also, presenting the causes that negatively affected the level of high school students, mainly in the Arabic language. Moreover, this study will diagnose the positive sides, of Arabic language learning, un order to enhance them, and the negative sides to give them much time and effort to achieve fruitful results in the near future.The study adopted the descriptive analytical method which served as a tool to analyze the content. The research sample contained the pedagogical instructions as well as the programs that are stated specifically for Arabic language teaching at the high school level. In addition to the Arabic textbook of the first year baccalaureate students of lettres and human sciences. The results of the study as follows:The learner’s low achievement in language science is due to: The difficulty of the subject itself, The dependence on the old approaches which mainly focus on the memorization and citation of the grammatical rules and examples, The learner’s psychological knot of the school subject, The unclearness of the teaching objectives of the school subject. , The high school Arabic textbook focuses on quantity instead of quality, The negative effects of the form and the content of the textbook on the learner, The presented educational experiences do not measure the evaluations.I finally found out that we have to rethink about the Arabic language teaching system according to the objectives that are already stated in the curriculum. Then, it is highly important to test the Arabic language textbook before applying it. Especially. In what concerns the lessons, the exercises, the examples , and the content as a whole which should suit the age and the educational level of the student. So that we can realize the goals that have been already put. In addition to that, we need to encourage teaching language sciences through adopting an activity-based learning approach. So that the students can be independent and learn through doing things rather than memorizing and repeating grammar rules without knowing their use.
Keywords: teaching; Language Science; High school qualification; Seiko's pedagogical approach